2001
DOI: 10.1021/ma0103268
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Substrate Interactions in Liquid Chromatography of Star Homopolymers and Star Block Copolymers

Abstract: A theoretical study of the behavior in liquid chromatography of star polymers of two different kinds of arms is presented, including the special cases of diblock copolymers and regular star polymers. The two different kinds of interactions between the substrate and the monomeric units which can be repulsive attractive or neutral combine in these heteroarm stars. They can act cooperatively or antagonistically determining, in connection with the effects of the architecture and the sizes of the branches, the mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…The critical condition is usually defined as the point at which the weak attractive enthalpic interaction effect is exactly compensated by the entropic exclusion effect for a linear homopolymer, and the polymer species elutes near the elution time of the injection solvent, independent of its molecular weight. ,, LCCC has been successfully employed for the characterization of a variety of complex polymer systems such as functionality analysis, polymer blends, block copolymers, stereoregularity analysis, cyclic polymers, etc. The LCCC retention of branched polymers has been also examined theoretically by several authors. , In the theoretical works, an ideal chain model was employed to calculate the partition coefficient of branched polymers in a pore. Theoretical calculations showed that if star-shaped polymers are chemically the same and are at the critical condition, the partition coefficient of the star-shaped polymers is independent of chain architecture.…”
Section: Introductionmentioning
confidence: 99%
“…The critical condition is usually defined as the point at which the weak attractive enthalpic interaction effect is exactly compensated by the entropic exclusion effect for a linear homopolymer, and the polymer species elutes near the elution time of the injection solvent, independent of its molecular weight. ,, LCCC has been successfully employed for the characterization of a variety of complex polymer systems such as functionality analysis, polymer blends, block copolymers, stereoregularity analysis, cyclic polymers, etc. The LCCC retention of branched polymers has been also examined theoretically by several authors. , In the theoretical works, an ideal chain model was employed to calculate the partition coefficient of branched polymers in a pore. Theoretical calculations showed that if star-shaped polymers are chemically the same and are at the critical condition, the partition coefficient of the star-shaped polymers is independent of chain architecture.…”
Section: Introductionmentioning
confidence: 99%
“…The differences in CAP for linear and branched chains have also been investigated theoretically and by computer simulations. The results of theoretical studies based on the Gaussian chain model showed that if the linear and branched polymers are chemically identical, their partition coefficients (LC retention) are essentially the same at the CAP of the linear polymers. Computer simulation using the lattice-based random walk model also yielded practically the same result. , They showed that, for the random walk case, both linear and branched polymers exhibit CAP behavior at the same interaction energy between the polymer segment and the pore wall (i.e., same T CAP for linear and star-shaped polymers) while the partition coefficient of star-shaped polymers is slightly larger than that of linear polymers ( t E, star > t E, linear ). The small difference was attributed to the chain-end effect, i.e., the absence of the neighboring repeating unit, and t E, star increases as the number of arms increases at the same overall MW.…”
Section: Introductionmentioning
confidence: 99%
“…That would result in a topology-independent elution under critical conditions for linear and branched polymers. Kosmas et al derived equations for the elution behavior of star polymers and predicted also identical critical elution behavior of linear and star polymers . However, Wang et al , emphasized the importance of the excluded volume interaction which was not taken into account in Guttman’s calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Kosmas et al derived equations for the elution behavior of star polymers and predicted also identical critical elution behavior of linear and star polymers. 22 However, Wang et al 23,24 emphasized the importance of the excluded volume interaction which was not taken into account in Guttman's calculations. Wang pointed out that the excluded volume has a nontrivial effect on polymers eluting at critical conditions.…”
Section: Introductionmentioning
confidence: 99%